Learning Mahaarah Al-Qiraa'ah Using Hijaiyyah Card Media in Islamic Elementary Schools - Salsabila Amanda; Hotimin Hotimin; Mulhendra Mulhendra (Publikasi Indonesia, 2024)
Mahaarah al-qiraa`ah plays an essential role in a person’s life, especially for students, so learning is also needed to help with teaching and learning activities. This research investigates the supporting and inhibiting factors in learning maharajah al-qiraa`ah using hijaiyyah letter card media. This research uses a qualitative approach with a case study method. Data was collected using interviews, observations, and documentation. The collected data in words is analyzed by reducing data, presenting data, and drawing conclusions. The results show that students' high enthusiasm and motivation support learning. The inhibiting factor is the lack of time for learning using hijaiyyah letter card media; classroom conditions were less conducive because some students interfered with other students.